Modulation of human dorsal root ganglion neuron firing by the Nav1.8 inhibitor suzetrigine - Robert G. Stewart; Tomás Osorno; Akie Fujita; Sooyeon Jo; Alyssa Ferraiuolo; Kevin Carlin; Bruce P. Bean (Proceedings of the National Academy of Sciences, 2025)
Nav1.8 voltage-gated sodium channels are strongly expressed in human primary pain-sensing neurons (nociceptors) and a selective Nav1.8 inhibitor VX-548 (suzetrigine) has shown efficacy for treating acute pain in clinical trials. Nociceptors also express other sodium channels, notably Nav1.7, raising the question of how effectively excitability of the neurons is reduced by inhibition of Nav1.8 channels alone. We used VX-548 to explore this question, recording from dissociated human dorsal root ganglion neurons at 37 °C. Applying VX-548 at 10 nM (about 25 times the IC 50 determined using cloned human Nav1.8 channels at 37 °C) had only small effects on action potential threshold and upstroke velocity but substantially reduced the peak and shoulder. Counterintuitively, VX-548 shortened the refractory period—likely reflecting reduced potassium channel activation by the smaller, narrower action potential—sometimes resulting in faster firing. Generally, repetitive firing during depolarizations was diminished but not eliminated by VX-548. Voltage clamp analysis suggested two reasons that repetitive firing often remains in 10 to 100 nM VX-548. First, many neurons had such large Nav1.8 currents that even 99% inhibition leaves nA-level Nav1.8 current that could help drive repetitive firing. Second, Nav1.7 current dominated during initial spikes and could also contribute to repetitive firing. The ability of human neurons to fire repetitively even with >99% inhibition of Nav1.8 channels may help explain the incomplete analgesia produced by even the largest concentrations of VX-548 in clinical studies.